2004
DOI: 10.1136/oem.2002.005199
|View full text |Cite
|
Sign up to set email alerts
|

Update of a prospective study of mortality and cancer incidence in the Australian petroleum industry

Abstract: Aims:To update the analysis of the cohort mortality and cancer incidence study of employees in the Australian petroleum industry.Methods:Employees from 1981 to 1996 were traced through the Australian National Death Index and the National Cancer Statistics Clearing House. Cause specific mortality and cancer incidence were compared with those of the Australian population by means of standardised mortality ratios (SMRs) and standardised incidence ratios (SIRs). Associations between increased incidence of specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 22 publications
0
70
0
Order By: Relevance
“…Studies of petroleum workers have shown an association between benzene exposure and leukemia [9][10][11][12]. Some studies of petroleum workers have found an elevated risk of multiple myeloma [13][14][15], while others have not [9,12,16]. Further, although a relation between non-Hodgkin lymphoma and benzene exposure has been suggested [7,8], most studies in the petroleum industry have not found any increased risk [5,17].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Studies of petroleum workers have shown an association between benzene exposure and leukemia [9][10][11][12]. Some studies of petroleum workers have found an elevated risk of multiple myeloma [13][14][15], while others have not [9,12,16]. Further, although a relation between non-Hodgkin lymphoma and benzene exposure has been suggested [7,8], most studies in the petroleum industry have not found any increased risk [5,17].…”
Section: Introductionmentioning
confidence: 90%
“…Studies of petroleum workers have shown an association between benzene exposure and leukemia [9][10][11][12]. Some studies of petroleum workers have found an elevated risk of multiple myeloma [13][14][15], while others have not [9,12,16].…”
Section: Introductionmentioning
confidence: 97%
“…While benzene (Group 1) (IARC 1987) and ethylbenzene (Group 2b) (IARC 2000) have been classified as carcinogens, the main concern for exposures to toluene and xylene are their effects on the central nervous system. Studies performed in the upstream petroleum industry have reported wide ranges of volatile organic hydrocarbon concentrations measured in air (Verma et al 2000;Glass et al 2000;Steinsvåg et al 2007;Bråtveit et al 2007;Runion 1988;Kirkeleit et al 2006a), as well as increased risk of cancer types that has been associated with these hydrocarbons such as leukemia (Glass et al 2003;Kirkeleit et al 2008;Aas et al 2009), multiple myeloma (Kirkeleit et al 2008), malignant melanoma (Lewis et al 2000;Sorahan et al 2002;Gun et al 2004Gun et al , 2006Christie et al 1991;Wong and Raabe 2000), and kidney cancer (Gun et al 2006).…”
Section: Introductionmentioning
confidence: 94%
“…Relative risks have been near unity in petroleum worker cohort studies in California, 177,178 Texas, [179][180][181] Louisiana, 182,183 US, [184][185][186] Canada 187,188 and Australia. 189 Inconsistent nonsignificant associations were found in an updated (1970-1997) mortality cohort study of 2 refinery/petrochemical plants (SMR for Baton Rouge facility 5 1.47, 95% CI: 0.98-2.11; SMR for Baytown facility 5 0.84, 95% CI: 0.47-1.39). 190 No significant associations between occupation in the oil industry (OR 5 0.94, 95% CI: 0.46-1.89) or occupational exposure to petroleum products (OR 5 1.2, 95% CI: 0.7-2.2) and risk of NHL were reported in 2 large case-control studies.…”
Section: Occupational and Environmental Chemical Exposurementioning
confidence: 99%